2000
DOI: 10.1038/labinvest.3780109
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Borrelia Burgdorferi in the Nervous System and Other Organs in a Nonhuman Primate Model of Lyme Disease

Abstract: SUMMARY:Lyme borreliosis is caused by infection with the spirochete Borrelia burgdorferi. Nonhuman primates inoculated with the N40 strain of B. burgdorferi develop infection of multiple tissues, including the central (CNS) and peripheral nervous system. In immunocompetent nonhuman primates, spirochetes are present in low numbers in tissues. For this reason, it has been difficult to study their localization and changes in expression of surface proteins. To further investigate this, we inoculated four immunosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 57 publications
6
95
0
1
Order By: Relevance
“…A previous report from our group described significant cardiac inflammation and tissue injury in the heart of immunosuppressed NHPs infected with the BbN40 strain. 6 We had also seen extensive cardiac injury in the heart of mice with severe combined immunodeficiency infected with B. turicatae. 18 In humans with Lyme disease, carditis is found in up to 25%, but only rarely pathology specimens are available for examination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous report from our group described significant cardiac inflammation and tissue injury in the heart of immunosuppressed NHPs infected with the BbN40 strain. 6 We had also seen extensive cardiac injury in the heart of mice with severe combined immunodeficiency infected with B. turicatae. 18 In humans with Lyme disease, carditis is found in up to 25%, but only rarely pathology specimens are available for examination.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Antigen retrieval by microwave heating (Dako's target retrival solution, Code No. S1699) or protease digestion (P-6911, Sigma Protease) was used with formalinfixed tissues.…”
Section: Immunohistochemistry and Image Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with chronic Lyme disease may have prolonged musculoskeletal or neurologic symptoms that cause significant morbidity. Studies in animals and humans with Lyme disease have shown persistence of spirochete DNA in various tissues, even after appropriate antibiotic therapy [2,3,4].…”
Section: Introductionmentioning
confidence: 99%